Improvements in PCOS characteristics and phenotype severity during a randomized controlled lifestyle intervention. Issue 2 (August 2021) - Dietz de Loos, Alexandra L.P.; Jiskoot, Geranne; Timman, Reinier; Beerthuizen, Annemerle; Busschbach, Jan J.V.; Laven, Joop S.E.
Abstract: Research question: What is the effect of weight loss through different interventions (three-component lifestyle intervention with short message service [SMS+] versus three-component lifestyle intervention without SMS [SMS–] versus care as usual [CAU]) on polycystic ovary syndrome (PCOS) characteristics (ovulatory dysfunction, hyperandrogenism, polycystic ovarian morphology [PCOM]) and phenotype distribution? Design: Analysis of secondary outcome measures of a randomized controlled trial. Women diagnosed with PCOS ( n = 183), who wished to become pregnant, with a body mass index above 25 kg/m², were assigned to a 1-year three-component (cognitive behavioural therapy, diet, exercise) lifestyle intervention group, with or without SMS, or to CAU (advice to lose weight). Results: The prevalence of biochemical hyperandrogenism was 30.9% less in the SMS- group compared with CAU after 1 year ( P = 0.027). Within-group analyses revealed significant improvements in ovulatory dysfunction (SMS+: –39.8%, P = 0.001; SMS–: –30.5%, P = 0.001; CAU: –32.1%, P < 0.001), biochemical hyperandrogenism (SMS–: –27.8%, P = 0.007) and PCOM (SMS–: –14.0%, P = 0.034). Weight loss had a significantly favourable effect on the chance of having ovulatory dysfunction (estimate 0.157 SE 0.030, P < 0.001) and hyperandrogenism (estimate 0.097 SE 0.027, P < 0.001). Conclusions: All groups demonstrated improvements in PCOS characteristics, although these were more profound within the lifestyle intervention groups. Weight loss per se led to an amelioration of diagnostic characteristics and in the phenotype of PCOS. A three-component lifestyle intervention aimed at a 5–10% weight loss should be recommended for all women with PCOS before they become pregnant.